EVALUASI TERHADAP KEPUTUSAN KELAYAKAN BISNIS PEMBANGUNAN PROYEK APARTEMEN SQR JAKARTA SELATAN DIMASA PANDEMI COVID-19 - Erna Rita Martiani; mulyantini, Sri (2022)
This study aims to analyze the factors behind the decision-making behavior of the SQR Apartment business feasibility. In addition, this study also aims to evaluate the business feasibility decisions of the SQR Apartment project during the covid-19 pandemic and to provide an alternative strategy for the SQR Apartment project during the covid-19 pandemic. The research methodology uses descriptive qualitative methods, researchers conduct in-depth interviews and collect objective data directly at the research site, namely the SQR apartment, and then process the data and validate the data obtained. For the purpose of the first study, the data was obtained from in-depth interviews with SQR management, for the second purpose, the data was obtained from the documentation of project realization of the business decision executors, and for the third purpose, the data was obtained from the results of management interviews. The results of this study indicate that decision-making from aspects of business feasibility is motivated by the planned behavioral factor. The results of the business evaluation with the plan and actual comparison method show that this project needs to be re-evaluated because there is too much deviation.